2011
DOI: 10.1021/jp2020897
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Supported Fe–Nx Catalysts Synthesized by Pyrolysis of the Fe(II)–2,3,5,6-Tetra(2-pyridyl)pyrazine Complex: Structure, Electrochemical Properties, and Oxygen Reduction Reaction Activity

Abstract: Carbon-supported Fe–N x /C catalysts were synthesized at several pyrolysis temperatures such as 600, 700, 800, and 900 °C in the effort to investigate the temperature effect on the catalyst structures. The Fe contents in the synthesized catalysts were found to be about 1 wt % more than that in the Fe–TPPZ/C precursor complex (5 wt %), indicating that both the carbon support and complex ligand might be decomposed during the pyrolysis. X-ray diffraction (XRD) analysis revealed that the samples at 600–800 °C had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 65 publications
6
48
0
Order By: Relevance
“…Among these peaks of N1s, pyridinic-N and graphitic-N play critical roles in determining the electrocatalytic ORR activity and stability of macrocycles. On the other hand, pyridine-N-oxide seems useless in improving the activity [44,45]. As show in Fig.…”
Section: Xps Analysismentioning
confidence: 95%
“…Among these peaks of N1s, pyridinic-N and graphitic-N play critical roles in determining the electrocatalytic ORR activity and stability of macrocycles. On the other hand, pyridine-N-oxide seems useless in improving the activity [44,45]. As show in Fig.…”
Section: Xps Analysismentioning
confidence: 95%
“…The structures of active sites on these Fe-based catalysts have been proposed by different groups including the structure of in-plane coordination of an iron atom and four pyridinic or pyrrolic type of nitrogen atoms embedded in a graphene-type matrix (Fe-N4/C [16,17,56,59,60] or Fe-N2+2/C [61]), the structure of coordination of an iron atom iron and two pyridinic type of nitrogen atoms embedded in a graphene-type matrix (Fe-N2/C) [60] and N-doped carbon-based structure (N-C) [62,63]. The factors of influence on ORR catalytic activity and stability of Fe-based catalysts have also been studied such as ring substituent group of non-pyrolyzed Fe-based macrocycle compounds [64,65], heat-treatment conditions [64,66,67], Fe content [68] and carbon support properties including surface nitrogen content and microporosity [31,57,69,70]. In order to produce highly active and stable Fe-based catalysts, ample approaches have been used with significant emphasis on introducing the exact effect of synthesis conditions and the nature of the catalytically active sites.…”
Section: Fe-based Catalystsmentioning
confidence: 99%
“…Although the Fe-based catalysts prepared via heat-treatment iron phthalocyanines (Pc)/porphyrins and their derivatives supported on carbon materials or some synthesized Fe-based macrocycle compounds seems to be a little complicated or high-cost relative to pyrolysis of transition metal salt carbon support, and nitrogen-rich small molecule, still plays an important role in the preparation of ORR catalysts and research of ORR active sites. It is not a unique instance, a new kind of highly active material, N-doped Fe or Fe3C encapsulated in carbon support (CNTs or Graphitic layers), has been reported by many groups [39,67,87,[94][95][96][97]. In 2012, Chen et al [94] reported a synthetic strategy that enables synthesis of nitrogen-enriched core-shell structured catalysts with iron-based composite (Fe/Fe3C) nanorods as the core and graphite carbon as the shell (N-Fe/Fe3C@C) ( Figure 5a).…”
Section: Preparation Of Fe-based Materials Toward Orrmentioning
confidence: 99%
“…In order to improve the catalytic activity and the stability, various nitrogen-containing ligands that are used as precursors to form Co-or Fe-complexes have been reported. [13][14][15][16][19][20][21] However, to the best of our knowledge, the ligand containing nitrogen and sulfur is rarely reported. Otherwise, some of nitrogen-containing ligands cannot easily achieve large-scale production due to their complex structures and high costs.…”
Section: Introductionmentioning
confidence: 99%